Manajemen Kegiatan Ekstrakurikuler dalam Peningkatan Skill Peserta Didik - Riska Zulka Amanda (IAIN Manado, 2023)
Management of Extracurricular Activities in Improving Student’s Skills. This research is to describe the improvement of students' skills through extracurricular activities. This research is a qualitative type with a descriptive approach. The research location was in the Madinatuddiniyyah integrated dayah Jabalnur Paloh Lada, Dewantara District, North Aceh Regency. The results of this study indicate that the Islamic boarding school not only facilitates extracurricular activities to improve students' skills, but other efforts are made to motivate students to improve their skills, namely holding competitions in the internal environment and participating in competitions in the external environment. The purpose of providing motivation is to encourage students to continue to work in earnest so that educational institutions will produce quality output and good management of extracurricular activities will ensure a positive impact on both students and educational institutions